Developing Islamic-Based Tourism Strategies for Sustainable Rural Independence: A Case Study of Kutawaringin Village, Indonesia - Uus Putria; Farhan Fauzan Salsabila (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study examines the potential of developing Kutawaringin Village, Indonesia, as a sustainable Islamic-based tourism destination, integrating the creative economy, nature tourism, and halal culinary practices. The objectives are to (1) analyze the internal and external factors affecting Kampung Jeans as a tourism village, (2) explore how Islamic values can be incorporated into strategic planning for rural tourism development, and (3) assess the potential impact of tourism on rural independence from an Islamic perspective. Using a qualitative approach with descriptive analysis and SWOT analysis, primary data was collected from observations and interviews with local communities. The findings reveal strengths such as the village’s historical identity in garment manufacturing, natural resources, and community institutions. However, weaknesses like limited human resource capacity and a fragmented tourism strategy pose challenges. Opportunities exist in the global halal tourism trend and the growing demand for nature and cultural tourism. The study concludes that integrating Islamic values such as maqāṣid al-sharī‘ah (Islamic objectives) and khilāfah (stewardship) can guide the village's sustainable tourism model. Implementing DSN-MUI Fatwa No. 108/2016 is essential to ensure Shari‘ah compliance, which is crucial for long-term success.